Pros and Cons of Application of Extraterritorial Jurisdiction in International Law: Various Practices in Southeast Asian Countries - Aryudhanty, Desvia Dwi; Yen, Lam Thong; Chan, Nai Jan (International Law Discourse in Southeast Asia, 2023)
The concept of extraterritorial jurisdiction in international law has garnered significant attention due to its implications on sovereignty, human rights, and global governance. This paper explores the diverse practices and approaches towards extraterritorial jurisdiction in Southeast Asian countries, considering both the advantages and disadvantages associated with its application. The pros of extraterritorial jurisdiction include the ability to hold individuals and entities accountable for actions committed beyond national borders, thereby addressing transnational crimes, ensuring justice for victims, and upholding international norms and standards. Furthermore, it can serve as a deterrent against cross-border offenses, promoting stability and security in the region. However, the application of extraterritorial jurisdiction also raises several concerns and challenges. One of the primary drawbacks is the potential infringement upon state sovereignty, as it involves the assertion of legal authority over foreign territories and nationals. This could lead to tensions between states and undermine diplomatic relations. Moreover, inconsistent or unilateral application of extraterritorial jurisdiction may result in legal uncertainty and conflicts of laws, hindering international cooperation and legal harmonization efforts. By examining the various practices in Southeast Asian countries, including legislative frameworks, judicial decisions, and diplomatic engagements, this paper aims to provide insights into the complexities surrounding the application of extraterritorial jurisdiction in the region. It underscores the need for balanced approaches that reconcile the pursuit of justice with respect for sovereignty and international law principles. Additionally, it highlights the importance of multilateral cooperation and dialogue in addressing transnational challenges while safeguarding the rights and interests of all stakeholders involved. Overall, this analysis contributes to a better understanding of the nuanced dynamics shaping the debate on extraterritorial jurisdiction in international law and its implications for Southeast Asia's legal landscape and regional cooperation mechanisms.